"Everything was blood when it comes to me": Understanding the lived experiences of women with inherited bleeding disorders. (21st October 2020) - Arya, Sumedha; Wilton, Pamela; Page, David; Boma‐Fischer, Laurence; Floros, Georgina; Winikoff, Rochelle; Teitel, Jerome; Dainty, Katie; Sholzberg, Michelle
Abstract: Introduction: Despite the many symptoms that women with inherited bleeding disorders experience, no study has specifically sought to explore and understand the lived experiences of these women, nor the barriers to care that they may encounter. The primary objective of this study was to describe the lived experiences of women with inherited bleeding disorders. Methods: Inclusion criteria for study enrollment were the following: age ≥18 years, English speaking, and confirmed diagnosis of an inherited bleeding disorder. Women were recruited across Canada through identification by treating health‐care providers and study members of the Canadian Hemophilia Society. Telephone interviews were conducted using a semi‐structured interview style, transcribed verbatim, and analyzed using descriptive thematic analysis. Results: A total of 15 participants were interviewed. Median age was 31 years (24–70 years old). Four primary themes emerged: uncertainties surrounding diagnosis, conceptualization of experience through family bleeding, intensity of bleeding symptoms, and impact of bleeding on identity and daily life. Discussion: To our knowledge, this is the first study to thoroughly describe the experiences of adult women living with inherited bleeding disorders. We found that these women experience multiple uncertainties around their diagnosis. They conceptualize their bleeding by examining family histories; experience severe symptoms irrespective of their underlying diagnosis; and create identities around their bleeding symptoms, which influence multiple aspects of their life. Next study steps will involve sharing work specifically focused on treatment plans, barriers to care, and factors affecting care access.